Broad Scale Coastal Simulation New Techniques to Understand and Manage Shorelines in the Third Millennium - Nicholls, Robert J.; Dawson, Richard J.; Day (née Nicholson-Cole), Sophie A. (Advances in Global Change Research, 2015)
This volume details research underpinning the 'Coastal Simulator' developed by the Tyndall Centre for Climate Change Research. The Simulator provides a framework to analyze long term coastal evolution taking account of all the relevant factors. These include the uncertain future climate and other conditions, such as land use change and allows evaluation of diverse management responses. Coastal zones exemplify the environmental pressures we face: their beauty attracts settlement, they offer potential for diverse economic activities, and they are sensitive natural habitats for important species, as well as providing a range of ecosystem services. They are also extremely vulnerable to the vicissitudes of climate change, which include rising sea levels and changes in extreme events such as storms. With large populations living in coastal and estuarine cities facing the ongoing threat of inundation, coordinated management is essential, especially as coastal zones form a linked system in which piecemeal, uncoordinated management could be counterproductive. The Simulator's current detailed application to the Norfolk coast goes from global climate modelling and broad socio-economic change to the details of evolving coastal habitats, coastal erosion and coastal flood risk and their societal implications. This framework reflects the work of a multi-disciplinary team of key players who analysed these diverse factors in a coherent and integrated manner. The book offers a compelling synthesis of the lessons learned so far at national and international levels, drawing on the expertise of policy makers as well as respected figures in the field.